Compassion or condemnation? South African Muslim students' attitudes to people with HIV/AIDS - Zubeda Paruk; Sitti Djamela Mohamed; Cynthia Patel; Sarojini Ramgoon (Taylor & Francis Group, 2006)
Given the dearth of literature on the influence of religiosity on attitudes toward people with HIV/AIDS, the present study surveyed these variables in a sample of South African Muslim university students using the Religious Orientation Scale (ROS) and an attitude to people with HIV scale. Gender differences in attitudes towards people with HIV were also examined. The sample comprised 90 male and female undergraduate and postgraduate Muslim students. While both males and females displayed high religiosity scores, male students were found to be significantly more religious than female students. No gender differences were found on the attitude to people with HIV scale, with students indicating positive attitudes to people with HIV. Higher religiosity was significantly correlated with a more positive attitude to people with HIV. The implications of the findings are discussed.